An Analysis of Biographies in Collective Memory Research: The Method of Socio-Historical Analysis - Karacan, Elifcan (Qualitative Sociology Review, 2019)
This article explores the use of biographies in qualitative research about collective memory. It is argued that commemorative ceremonies, as well as changes appearing in macro-level structures within the time-span of individuals’ life histories need to be included when analyzing biographies in collective memory studies. The article suggests enhancement of the biographical case reconstruction method (Rosenthal 1993; 2004) with two additional stages: analysis of the experienced past with more emphasis on socio-historical transformations; and inclusion and analysis of the ethnographical data collected from collective mnemonic practices. By providing empirical data from the research conducted with political exiles in Germany, these analytical steps of the method of socio-historical analysis are demonstrated in detail.